Contribution and compatibility of public open space in disaster management: Perception and experience from Kathmandu Metropolitan - Timalsina, Krishna Prasad; Subedi, Bhim Prasad; Sapkota, Kanhaiya (Geographical Journal of Nepal, 2024)
Despite the extensive literature on public open space (POS) in urban settings, its role in disaster risk reduction and management(DRRM) as perceived and experienced by its residents is limited. Taking a case from Kathmandu Metropolitan City (KMC), this paper analyzes the role and suitability of POS in DRRM. It focuses on: (a) how urban residents perceive and experience the linkages between POS and DRRM, (b) how they utilized the POS during disasters, and in what ways they were instrumental in helping disaster victims,and (c) to what extent the existing POSs are compatible for DRRM in dense urban areas. This study uses qualitative research methodology employing POS inventory taking, key informant interviews, in-depth interviews, and field observation as research instruments. The result of the study shows that people's perception on the use of POS during disasters was very positive and these spaces were intrinsically utilized during disasters in the metropolitan Kathmandu. However, their effectiveness and compatibility in DRRM were contingent upon contextual factors, the inherent nature and types of POS, and the extent of accessibility to them.